Comparison of The Number of Macrophage in Full Thickness Wound Incision between Merremia mammosa Extract Treatment and NaCl in Male Wistar Rats - Hidayat, Fajar Kurniawan; Elfiah, Ulfa; Sofiana, Kristianningrum Dian (Journal of Agromedicine and Medical Sciences, 2015)
The incidence of diabetes mellitus in Indonesia continues to increase. There are some complications in the diabetic condition, one of which is diabetic ulcer. Diabetic ulcers in diabetes patient can increase the risk of amputation and expensive treatment costs, so the alternative treatmeant such as Merremia mammosa wich has antiinflamatory and antidiabetic is needed. This study aimed to determine the comparison of the number of macrophage in the incisional wound in hyperglycemic male wistar rats between treatment with Merremia mammosa extract and NaCl. The in vivo test was done by creating wound incision on the mice backs and treated with gentamycin ointment 5% in a positive control group, NaCl in a negative control group and Merremia mammosa extract in a dose of 100m), 200mg, 400mg in treatment group. The result obtained by counting the number of macrophage in histopatholgy examination. The result showed the number of macrophage were 0,36 cells/field of view in a negative control group, 0,52 cells/field of view in a positive control group, 0,48 cells/field of view in all Merremia mammosa treatment groups. The data analysis showed no significant difference with p-value of 0,729. In conclusion, there was no significant difference between the used of Merremia mammosa extract and NaCl on full thickness incisional wounds of hyperglycemic male wistar rats. Keywords: Diabetes Mellitus, Merremia mammosa extract, incisional wound